2012
DOI: 10.1016/j.jhealeco.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Marginal benefit incidence of public health spending: Evidence from Indonesian sub-national data

Abstract: We examine the marginal effects of decentralized public health spending by incorporating estimates of behavioural responses to changes in health spending in benefit incidence analysis. The analysis is based on a panel dataset of 207 Indonesian districts over the period from 2001 to 2004. We show that district public health spending is largely driven by central government transfers, with an elasticity of around 0.9. We find a positive effect of public health spending on utilization of outpatient care in the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 13 publications
2
13
0
2
Order By: Relevance
“…After decentralization, increased fiscal independence at the district level was recognized in the majority of districts across Indonesia. 49,50 The increase allowed DHO to manage their spending and prioritize according to their local health needs. However, in Bantul, Mataram, Kutai Kartanegara, and Ngada districts, budget constraints were more common after decentralization than before, due to public health budget reduction.…”
Section: Who Building Block: Financingmentioning
confidence: 99%
“…After decentralization, increased fiscal independence at the district level was recognized in the majority of districts across Indonesia. 49,50 The increase allowed DHO to manage their spending and prioritize according to their local health needs. However, in Bantul, Mataram, Kutai Kartanegara, and Ngada districts, budget constraints were more common after decentralization than before, due to public health budget reduction.…”
Section: Who Building Block: Financingmentioning
confidence: 99%
“…It generally examines only health care consumption and coverage rather than health outcomes, and looks at the average benefits of current expenditure rather than the marginal benefits of potential future changes in expenditure. Some recent benefit incidence analyses, however, have used data on subnational variation and change in expenditure and outcomes to estimate the health outcomes of marginal changes in spending in a way that could be used more directly to inform priority setting [44].…”
Section: Equity Impact Analysismentioning
confidence: 99%
“…There are studies, such as those by Chakraborty, Singh, and Jacob (2013) for India; and Kruse, Pradhan, and Sparrow (2012) for Indonesia, that examine the distribution of benefits from public health spending, by income groups in general, or from health-care financing reforms. Examining both inpatient and outpatient health services, Chakraborty, Singh, and Jacob (2013) found that India's public health expenditure tends to be inequitable.…”
Section: Public Spending On Health Carementioning
confidence: 99%
“…The poorest quintile captured around 9% of the total net public expenditure in the health sector, while the richest group got around 40%. On the other hand, for Indonesia, Kruse, Pradhan, and Sparrow (2012) found that the health system tends to be pro-poor as increased local public health spending led to net transfers from the richest to the poorest quarter of the population, which increased public health-care utilization by the poor and average health benefits. Given initial utilization shares, however, the bulk of the benefits were still captured by the middle-income groups; thus, it was recommended that increased public health spending be complemented by more directly targeted demand-side interventions for the poor, such as price subsidies or social health insurance.…”
Section: Public Spending On Health Carementioning
confidence: 99%